Subdivision of flagellar genes of Salmonella typhimurium into regions responsible for assembly, rotation, and switching. - Yamaguchi, S (1986)
Three flagellar genes of Salmonella typhimurium (flaAII.2, flaQ, and flaN) were found to be multifunctional, each being associated with four distinct mutant phenotypes: nonflagellate (Fla-), paralyzed (Mot-), nonchemotactic (Che-) with clockwise motor bias, and nonchemotactic (Che-) with counterclockwise motor bias. The distribution of Fla, Mot, and Che mutational sites within each gene was examined. Fla sites were fairly broadly distributed, whereas Mot and Che sites were more narrowly defined. Local subregions rich in sites of one type were not generally rich in sites of another type. Among Che sites, there was little overlap between those corresponding to a clockwise bias and those corresponding to a counterclockwise bias. Our results suggest that within the corresponding gene products there are specialized subregions for flagellar structure, motor rotation, and control of the sense of rotation.